(untitled) (Research, Society and Development, 2020)
This study was carried out to evaluate the production indexes of the Mangalarga Marchador horse farms, in which horse’s breeders were interviewed. The survey with 244 questions, where 262 variables were analyzed, of which 28 were used for the evaluation of productivity. The average number of births per farm/year throughout the Rio de Janeiro is 22.7 foals, which is equivalent to 42.5%, an average, of mares available for breeding. The birth rate is 94% throughout the Rio de Janeiro. More than 60% of stud farms have a mare’s productivity index above 0.5, with the highest average for the Northwestern Fluminense mesoregion (0.70) and the lowest for the Central Fluminense mesoregion (0.52). The ratio between pregnant/donor recipients mares shows an average of 1.96 embryos conceived by donor, considering all farms in the State of Rio de Janeiro. The highest average was observed in the Northwestern mesoregion (2.20 embryos per donor) and the lowest in the Southern Fluminense mesoregion (1.72 embryos per donor). The artificial insemination using a stallion on the farm is greater than the use of natural mating, especially in the mesoregions where fertility rates in embryo transfer are higher. The productivity rate presented an average of 0.23 considering all farms in the State of Rio de Janeiro, and ranged from 0.20 to 0.26 in the Central and Northwestern Fluminense mesoregions, respectively. The Northwestern mesoregion presented the best average productivity index of the Mangalarga Marchador herd in the state of Rio de Janeiro.